Long-term evaluation of lipid profile changes in Olympic athletes - Di Gioia, G.; Buzzelli, L.; Maestrini, V.; Squeo, M. R.; Lemme, E.; Monosilio, S.; Serdoz, A.; Fiore, R.; Zampaglione, D.; Segreti, A.; Pelliccia, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Dyslipidemia is a major contributor to the development of atherosclerotic cardiovascular disease. Despite high level of physical activity, athletes are not immune from dyslipidemia, but longitudinal data on the variation of lipids are currently lacking. We sought to assess lipid profile changes over time in Olympic athletes practicing different sports disciplines (power, skills, endurance, and mixed). We enrolled 957 consecutive athletes evaluated from London 2012 to Beijing 2022 Olympic Games. Dyslipidemia was defined as low-density lipoprotein (LDL) =115 mg/dl, high-density lipoprotein (HDL) <40 mg/dl for males, or HDL <50 mg/dl for females. Hypertriglyceridemia was defined as triglycerides >150 mg/dl. At the follow-up, a variation of ±40 mg/dl for LDL, ±6 mg/dl for HDL, and ±50 mg/dl for triglycerides was considered relevant. Athletes with follow-up <10 months or taking lower lipid agents were excluded. Follow-up was completed in 717 athletes (74.9%), with a mean duration of 55.6 months. Mean age was 27.2 ± 4.8 years old, 54.6% were male (n = 392). Overall, 19.8% (n = 142) athletes were dyslipidemic at both blood tests, being older, practicing nonendurance sports, and predominantly male. In 69.3% (n = 129) of those with elevated LDL at t0, altered values were confirmed at follow-up, while the same occurred in 36.5% (n = 15) with hypo-HDL and 5.3% (n = 1) in those with elevated triglycerides. Weight and fat mass percentage modifications did not affect lipid profile variation. LDL hypercholesterolemia tends to persist over time especially among male, older, and nonendurance athletes. LDL hypercholesterolemia detection in athletes should prompt early preventive intervention to reduce the risk of future development of atherosclerotic disease.